Trace Level Analysis Of Chromium, Manganese, Cobalt And Iron In Human Hair Of People Residing Near Heavy Traffic Area By Biomonitoring - RITA MEHRA,; AMIT SINGH THAKUR,; SEEMA BHALLA, (International Journal of Pharma and Bio Sciences, 2010)
Biomonitoring of Cr, Mn, Co and Fe in hair of 116 subjects of 40-50 years of age living near heavy traffic area and less traffic area in the state of Rajasthan in India was carried out. Out of these 116 subjects, 58 subjects lived near heavy traffic area and remaining 58 subjects lived near less traffic area. Head hair samples from nape region were personally collected using stainless steel scissor. All hair samples were washed with non-ionic detergent & acetone successively to remove external contamination and digested to get a colourless and clear solution followed by analysis using Atomic Absorption Spectrophotometer Perkin Elmer Model 5000 using air acetylene flame for Cr, Mn, Co and Fe concentrations. On appropriate statistical treatment of data, mean Cr and Mn level in hair of subjects living near heavy traffic area were found higher than subjects living near less traffic area. Mean Fe and Co levels in hair of subjects living near heavy traffic area were significantly less than subjects living near less traffic area.